2015
DOI: 10.2147/opth.s77538
|View full text |Cite
|
Sign up to set email alerts
|

Folate status in type 2 diabetic patients with and without retinopathy

Abstract: BackgroundFolate deficiency is associated with cardiovascular disease, megaloblastic anemia, and with hyperhomocysteinemia. This study has been undertaken to investigate the role of folate status during the progression of the diabetic retinopathy.MethodsWe measured the plasma levels of homocysteine, folic acid, and red cell folate in 70 diabetic type 2 patients with nonproliferative diabetic retinopathy (NPDR), 65 with proliferative diabetic retinopathy (PDR), 96 without diabetic retinopathy, and 80 healthy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 26 publications
3
40
0
2
Order By: Relevance
“… 170 The authors found an association between folic acid/vitamin B6/vitamin B12 supplementation and protection against AMD development. An ongoing clinical study is also investigating the effects of folic acid, vitamin B6, and vitamin B12 supplementation on the progression of DR. 171 Folic acid is an upstream methyl donor for DNA methylation; vitamins B6 and B12 are involved as cofactors in the process of transferring the methyl group indirectly from folic acid to the DNA. Recent data suggest an association between dietary folic acid intake and global methylation levels.…”
Section: Future Directions: Epigenetics As Therapeuticsmentioning
confidence: 99%
“… 170 The authors found an association between folic acid/vitamin B6/vitamin B12 supplementation and protection against AMD development. An ongoing clinical study is also investigating the effects of folic acid, vitamin B6, and vitamin B12 supplementation on the progression of DR. 171 Folic acid is an upstream methyl donor for DNA methylation; vitamins B6 and B12 are involved as cofactors in the process of transferring the methyl group indirectly from folic acid to the DNA. Recent data suggest an association between dietary folic acid intake and global methylation levels.…”
Section: Future Directions: Epigenetics As Therapeuticsmentioning
confidence: 99%
“…There is evidence that pregnant women are at risk of folate deficiency due to an increased demand for FA . Moreover, hyperglycemia has been linked to reduced levels of FA . Thus, the risk of congenital malformations because of a FA‐deficient environment caused by hyperglycemic pregnancy may only worsen when combined with a genetic impairment in maternal folate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…58,63 Moreover, hyperglycemia has been linked to reduced levels of FA. 59,60,64 Thus, the risk of congenital malformations because of a FA-deficient environment caused by hyperglycemic pregnancy may only worsen when combined with a genetic impairment in maternal folate metabolism. Our preliminary experiments in vitro demonstrated that the phenotype of the embryos was affected by the presence of high levels of glucose, although the incidence of cranial or spinal NTDs did not increase when high glucose and high homocysteine conditions were combined.…”
Section: Embryonic But Not Maternal Folate Genetics Interaction Witmentioning
confidence: 99%
“…With regard to diabetic retinopathy, a direct effect has been demonstrated for folate deficiency by destabilizing the genes by demethylation, a source of aggravation of the retinal proliferative process [8].…”
Section: Discussionmentioning
confidence: 99%